Testing of new massive competition system - Stakvilevičius , M.; Dargis , F. (Psichologija, 1972)
The article describes experimental test of new massive competition system. Linear, Swiss and two-step systems were in test. Practical experience and modelling shows that new systems meet the actual sports needs better.
Keywords: sport competitions; competition systems